2020
DOI: 10.1002/mds.28176
|View full text |Cite
|
Sign up to set email alerts
|

COVID‐19 in Parkinson’s Disease Patients Living in Lombardy, Italy

Abstract: Background. It is unknown whether patients with Parkinson's disease (PD) are at greater risk of COVID-19, what their risk factors are and whether their clinical manifestations differ from the general population.Methods. In a case-controlled survey, we interviewed 1486 PD patients attending a single tertiary centre in Lombardy, Italy and 1207 family members (controls).Results. 105 (7.1%) and 92 controls (7.6%) were identified as COVID-19 cases. COVID-19 patients were younger, more likely to suffer from chronic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

13
203
5
8

Year Published

2020
2020
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 139 publications
(229 citation statements)
references
References 35 publications
13
203
5
8
Order By: Relevance
“…Clinical implications of SARS-CoV-2 infection on PD are largely speculative apart from two case series and case reports 45,46 . A community-based case control study in Italy of 12 PD COVID-19 cases suggested substantial worsening of motor and non-motor symptoms during mild to moderate COVID-19 illness, independent of age and disease duration 144 , in line with an original case report series by Antonini et al In another survey across the Lombardy region of Italy, 105 probable COVID-19 cases were identified and the authors concluded that the risk, morbidity, and mortality in patients with mild-to moderate PD with COVID-19 did not differ from the general population 145 . Several viewpoints and editorials have been published on the topic in addition to extensive coverage in social media and journal viewpoint papers [146][147][148][149][150][151] .…”
Section: The Clinical Perspectivesupporting
confidence: 63%
“…Clinical implications of SARS-CoV-2 infection on PD are largely speculative apart from two case series and case reports 45,46 . A community-based case control study in Italy of 12 PD COVID-19 cases suggested substantial worsening of motor and non-motor symptoms during mild to moderate COVID-19 illness, independent of age and disease duration 144 , in line with an original case report series by Antonini et al In another survey across the Lombardy region of Italy, 105 probable COVID-19 cases were identified and the authors concluded that the risk, morbidity, and mortality in patients with mild-to moderate PD with COVID-19 did not differ from the general population 145 . Several viewpoints and editorials have been published on the topic in addition to extensive coverage in social media and journal viewpoint papers [146][147][148][149][150][151] .…”
Section: The Clinical Perspectivesupporting
confidence: 63%
“…To date, only two case series for a total of 12 PD patients and one community-based study were published about PD and COVID-19 [3,4,6], suggesting worsening of motor and non-motor symptoms and an association between higher mortality rates (40%) and older age and longer PD duration [3,4]. Also, a recent large case-control study performed on a single-center in Lombardy, Italy, reported an interview to non-advanced PD patients [5]. The authors found a similar rate of infection in PD patients and controls and suggest that COVID-19 risk and mortality did not differ from the general population.…”
mentioning
confidence: 99%
“…The clinical outcomes included increased vitamin D levels, shorter lengths of hospital stay, lower oxygen requirements and reduced inflammatory markers. Another questionnaire-based study in Italy reported that vitamin D supplementation reduced the prevalence of COVID-19 infection (odds ratio, 0.56; 95% confidence interval, 0.32–0.99; p = 0.048) ( Fasano et al, 2020 ).…”
Section: Vitamin D and Acute Lung Injurymentioning
confidence: 99%